-6y+6=-2y(4y+6)

Simple and best practice solution for -6y+6=-2y(4y+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y+6=-2y(4y+6) equation:


Simplifying
-6y + 6 = -2y(4y + 6)

Reorder the terms:
6 + -6y = -2y(4y + 6)

Reorder the terms:
6 + -6y = -2y(6 + 4y)
6 + -6y = (6 * -2y + 4y * -2y)
6 + -6y = (-12y + -8y2)

Solving
6 + -6y = -12y + -8y2

Solving for variable 'y'.

Combine like terms: -6y + 12y = 6y
6 + 6y + 8y2 = -12y + -8y2 + 12y + 8y2

Reorder the terms:
6 + 6y + 8y2 = -12y + 12y + -8y2 + 8y2

Combine like terms: -12y + 12y = 0
6 + 6y + 8y2 = 0 + -8y2 + 8y2
6 + 6y + 8y2 = -8y2 + 8y2

Combine like terms: -8y2 + 8y2 = 0
6 + 6y + 8y2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(3 + 3y + 4y2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(3 + 3y + 4y2)' equal to zero and attempt to solve: Simplifying 3 + 3y + 4y2 = 0 Solving 3 + 3y + 4y2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. 0.75 + 0.75y + y2 = 0 Move the constant term to the right: Add '-0.75' to each side of the equation. 0.75 + 0.75y + -0.75 + y2 = 0 + -0.75 Reorder the terms: 0.75 + -0.75 + 0.75y + y2 = 0 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + 0.75y + y2 = 0 + -0.75 0.75y + y2 = 0 + -0.75 Combine like terms: 0 + -0.75 = -0.75 0.75y + y2 = -0.75 The y term is 0.75y. Take half its coefficient (0.375). Square it (0.140625) and add it to both sides. Add '0.140625' to each side of the equation. 0.75y + 0.140625 + y2 = -0.75 + 0.140625 Reorder the terms: 0.140625 + 0.75y + y2 = -0.75 + 0.140625 Combine like terms: -0.75 + 0.140625 = -0.609375 0.140625 + 0.75y + y2 = -0.609375 Factor a perfect square on the left side: (y + 0.375)(y + 0.375) = -0.609375 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x^2-1.62x-1=0 | | 25c-16=0 | | 20-42=5x+2+5x | | 15x-11=-41 | | 8z+9=8z-z | | 10-3c-7=-5 | | 5x-2+2x+6= | | 4(3+k)-7fork=0 | | 2-5(5v-8)=24-45v | | -3x+4x-3=-5 | | 384x+x=2494 | | 16r-4t-13t-17t= | | x^2+14x-68=4 | | 6y+5=4y+11 | | 5x^4567=5 | | 3=x^36 | | (-3i+4)*(3i+4)=25 | | (-3i+4)*(3i+4)= | | Z(z-12)=27 | | cx-ab=ax+d | | 1*(x-45)=x | | rx+rt=c | | 5x^2-20x=-11 | | 11x+7=6x+28 | | -5x+10=x+4 | | 5x^2-12x-40=0 | | 5x^2-20x=11 | | 2x^2+x+121+x^2-2x+49=180 | | 3x+4=-44+x+4-2x | | Tan(x)tan(5x)=1 | | 600=800m-600 | | 3x+4=-44+4-2x |

Equations solver categories